2004
DOI: 10.1016/j.tig.2003.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Riboswitches: the oldest mechanism for the regulation of gene expression?

Abstract: Riboswitches are structures that form in mRNA and regulate gene expression in bacteria. Unlike other known RNA regulatory structures, they are directly bound by small ligands. The mechanism by which gene expression is regulated involves the formation of alternative structures that, in the repressing conformation, cause premature termination of transcription or inhibition of translation initiation. Riboswitches regulate several metabolic pathways including the biosynthesis of vitamins (e.g. riboflavin, thiamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(187 citation statements)
references
References 49 publications
3
183
0
1
Order By: Relevance
“…The genes for transcribed proteins are fused to genes for a protein that fluoresces according to its expression, which correlates directly with glucose concentrations in blood plasma samples. Other authors have suggested repression of the operon containing genes for ribosomal proteins when the amount of free proteins exceeds the amount of ribosomal proteins, thus creating an on/off switch system [36,37]. A riboswitch has also been identified as a signaling mechanism in response to extreme environmental conditions such as oxidative stress [38].…”
Section: Discussionmentioning
confidence: 99%
“…The genes for transcribed proteins are fused to genes for a protein that fluoresces according to its expression, which correlates directly with glucose concentrations in blood plasma samples. Other authors have suggested repression of the operon containing genes for ribosomal proteins when the amount of free proteins exceeds the amount of ribosomal proteins, thus creating an on/off switch system [36,37]. A riboswitch has also been identified as a signaling mechanism in response to extreme environmental conditions such as oxidative stress [38].…”
Section: Discussionmentioning
confidence: 99%
“…the size of mitochondrial SSU mRNAs. The sequences are listed in Table 4 This range covers most of the important regulatory RNA elements that are dependent on refolding effects such as naturally occurring riboswitches (35), self-induced RNA switches as the hok family mRNAs (36) or the fine-tuned system of retarded cloverleaf formation in the case of bacteriophage MS2 (37), and makes them accessible to computational prediction.…”
Section: Runtimementioning
confidence: 99%
“…The best known example of such behavior are the riboswitches [423]. These are autonomous structural elements primarily found within the 5'-UTRs of bacterial mRNAs, which, upon direct binding of small organic molecules, can trigger conformational changes, leading to an alteration of the expression for the downstream located gene.…”
Section: Riboswitchesmentioning
confidence: 99%